Jak zostać dworzaninem Maryi…, czyli Samuela Brzeżewskiego Zaciąg dworzanów na kurię Najświętszej Królowej nieba i ziemi na kazaniu w dzień Jej narodzenia - Dybek, Dariusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
Samuel Brzeżewski is a long-forgotten Polish Baroque preacher. He left behind three written sermons, of which two take on Marian themes. Among those is Zaciąg dworzan.w na kurię Najświętszej Kr.lowej nieba i ziemi […] – „The recruitment of courtiers to the curia of the Blessed Queen of heaven and earth at a sermon on the day of her birth” (transl.), written in 1644 and published in 1645. It came into existence on the occasion of the anniversary of the birth of the Mother of God and has an interesting sermon-concept form. In spite of the fact that the author reached for the expression „queen”, from time immemorial applied with reference to Mary, he combined with it an interesting fictional plot by portraying the process of the recruiting of courtiers for the court of the queen (it is one of the few Old Polish texts referring to the manner of recruitment for the court of a monarch). Closer study of various desirable features of courtiers (beauty, education, bravery) leads Brzeżewski to arrive at the conclusion that the greatest opportunities for admission to the service of the Mother of God are gifted to „bandits” (i.e. hardened sinners rejected by all) and „agonizantes” (viz. the dying) – those to whom Mary shows her kindness and magnanimity.